Design automation for partially reconfigurable adaptive systems - Kizheppatt, Vipin (2015)
Adaptive systems have the ability to respond to environmental conditions, by modifying their processing at runtime. While this is easy to do in software systems, modern algorithms can be computationally expensive, requiring powerful processors. At the same time hardware is not as flexible. Field programmable gate arrays (FPGAs) are recognised as being suitable for adaptive systems implementation, due to their flexibility and high performance. New hybrid FPGA platforms which integrate able processors with reconfigurable fabric provide a new platform to further explore hardware reconfigurability. The use of partial reconfiguration (PR) on FPGAs to implement adaptive systems has been proposed many times in the literature. However the design process for partially reconfigurable systems is complex and requires specialist knowledge on behalf of the application designer. Hence, it has remained a rarely used capability outside of academic circles. We propose a new approach to leverage PR within adaptive systems, by integrating with, rather than circumventing, supported vendor tool flows, while automating many of the steps that have made such designs more difficult in the past. This makes it possible for system designers with less FPGA expertise to use PR when designing adaptive systems.